Determinants of financial and environmental disclosures through the internet by Malaysian companies - Al Arussi, AS; Selamat, MH; Hanefah, MM (Emerald Group Publishing Ltd, 2024)
Purpose - The purpose of this paper is to investigatewhether the voluntary financial and environmental disclosures through the internet can be explained by the same determinants as in conventional reporting. Specifically, this paper examines the relationship between the extent of financial and environmental disclosures on the internet and six variables, namely, ethnicity of chief executive officer (CEO), leverage, level of technology, existence of dominant personalities, profitability, and firm size. Design/methodology/approach - Six hypotheses were tested using data collected from 201 Malaysian listed companies on the Bursa Malaysia's Main and Second Boards for the financial year 2005. A regression model is utilized to analyze the results of this paper and this is in tandem with the previous studies. Findings - The results indicate that level of technology, ethnicity of CEO and firm size are determinants of both internet financial and environmental disclosures. However, the existence of a dominant personality is found to negatively affect the level of financial disclosures but not environmental disclosures. The other variables did not show any significant relationship with either financial or environmental disclosures. Originality/value - This paper investigates whether internet financial and environmental disclosures can be explained by the same determinants used in other similar studies. The results indicate that only level of technology, ethnicity of CEO and firm size are found to be significant for both internet financial and environmental disclosures.